Badger macrophages fail to produce nitric oxide, a key anti-mycobacterial effector molecule - Bilham, K; Boyd, A; Preston, S; Buesching, C; Newman, C; Macdonald, D; Smith, A (Springer Nature, 2017)
The European badger is recognised as a wildlife reservoir for bovine tuberculosis (bTB); the control of which is complex, costly and controversial. Despite the importance of badgers in bTB and the well-documented role for macrophages as anti-mycobacterial effector cells, badger macrophage (bdMĳ) responses remain uncharacterised. Here, we demonstrate that bdMĳ fail to produce nitric oxide (NO) or upregulate inducible nitric oxide synthase (iNOS) mRNA following Toll-like receptor (TLR) agonist treatment. BdMĳ also failed to make NO after stimulation with recombinant badger interferon gamma (bdIFNȖ) or a combination of bdIFNȖ and lipopolysaccharide. Exposure of bdMĳ to TLR agonists and/or bdIFNȖ resulted in upregulated cytokine (IL1ȕ, IL6, IL12 and TNFĮ) mRNA levels indicating that these critical pathways were otherwise intact. Although stimulation with most TLR agonists resulted in strong cytokine mRNA responses, weaker responses were evident after exposure to TLR9 agonists, potentially due to very low expression of TLR9 in bdMĳ. Both NO and TLR9 are important elements of innate immunity to mycobacteria, and these features of bdMĳ biology would impair their capacity to resist bTB infection. These findings have significant implications for the development of bTB management strategies, and support the use of vaccination to reduce bTB infection in badgers.